Mediatization and populism approach through media content analysis of newspapers during Sarawak’s election and midterm transition government 2020 - Mohd Nashriq Nizam; Hasmah Zanuddin; MMohamad Saleeh Rahamad (Penerbit Universiti Kebangsaan Malaysia, 2003)
This paper aims to investigate the relationship and adaptation of mediatization of politics with populism into media content of seven (7) Sarawak newspapers, namely Borneo Post, New Sarawak Tribune, Utusan Sarawak, Utusan Borneo, Suara Sarawak, See Hua Daily, and Sin Chew Daily during Sarawak's election and the Midterm Transition of Malaysia Government 2020 by using quantitative content analysis. The Hoslti Inter-coder reliability and validity, Chi-Square, and One-way ANOVA tests were used on 695 news items. The results demonstrate that the Hoslti Inter-coder reliability and validity averaged 93%, above 70%. The Chi-Square test proved the news headline, government initiation, government response, and blame attribution (substance blame and non-policy blame) at the 0.001 level (2 tailed p<0.0005), and we rejected the null hypothesis. As for opposition response, and blame attribution (substance and non-policy blame), the p-value is more significance level (2-tailed p>0.0005), and we do not reject the null hypothesis. For mediatization of politics, only two (2) issues under media logic have p-values above .05, which are conflict (0.054) and opinionated and narrative news articles (0.143) with F values of 6.957 and 6.364. In political logic, result showed that p-value is less than .05 which there is a statistically significant difference in newspaper coverage. Anti-elitism (0.161) has a p-value more significant than .05, with F value is 1.797 in populism. People-centrism and mistrust of experts have p-values less than .05. This results in a statistically significant difference in newspaper coverage.